2010
DOI: 10.4172/1948-593x.1000014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anthum Graveolens L. Extract on Biochemical and Histopathological Alteration of Deltamethrin in Rats

Abstract: Anthum graveolens (dill) seeds are a common and very effective household remedy for a wide range of digestive problems. The present study was performed to investigate the effect of dill extracts on altered biochemical parameters in deltamethrin-exposed rats. Deltamethrin was administered orally at doses 7.5 and 15 mg /kg of body weight on the basis of LD 50 for 30 days. The sub-acute toxicity of pyrethroid insecticide deltamethrin varies markedly with the dose employed. Oral administration of plant extracts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Serum GSH level as well as the liver GSH content and GST activity were significantly lower than those of the control ones after cypermethrin treatment (Tables 5 and 6). On the other hand, the present data revealed that vitamin E administration causes improvement in the oxidative status induced by cypermethrin causing the increase of GSH level (+49.25%) and the activity of GGT and GST in serum were also increased +55.89% and +32.87%, respectively in Table (6). These results are in agreement with those reported El-Maghraby et al (2010) who showed that administration of the chlorpyrifos and deltamethrin (DLM) caused damage in rat liver and also caused decrease in the activities of GST and DOS enzymes. Reda (2005) found that the activity of gamma glutamyl transferase (GGT) was increased and a marked reduction in each of liver glutathione (GSH) level and the activity of glutathione-s-transferase (GST) were also recorded.…”
Section: Effects Of Cypermthrin Vit E Zinc and Their Mixtures On Lsupporting
confidence: 93%
“…Serum GSH level as well as the liver GSH content and GST activity were significantly lower than those of the control ones after cypermethrin treatment (Tables 5 and 6). On the other hand, the present data revealed that vitamin E administration causes improvement in the oxidative status induced by cypermethrin causing the increase of GSH level (+49.25%) and the activity of GGT and GST in serum were also increased +55.89% and +32.87%, respectively in Table (6). These results are in agreement with those reported El-Maghraby et al (2010) who showed that administration of the chlorpyrifos and deltamethrin (DLM) caused damage in rat liver and also caused decrease in the activities of GST and DOS enzymes. Reda (2005) found that the activity of gamma glutamyl transferase (GGT) was increased and a marked reduction in each of liver glutathione (GSH) level and the activity of glutathione-s-transferase (GST) were also recorded.…”
Section: Effects Of Cypermthrin Vit E Zinc and Their Mixtures On Lsupporting
confidence: 93%
“…Glutathione S-transferase (GST) plays a key role in cellular detoxification by catalyzing the reaction of GSH with toxicants to form an S-substituted glutathione (Danyelle and Kenneth 2003). The elevation in hepatic, renal and spleen GST activity in presence of ascorbic acid in Pb or pesticide intoxicated animals are in agreement with the findings of Das et al (2009) andEl-Maghraby, Taha, andHassan (2010). The rise in expression of GPx and GST enzymes in ascorbic acid administered animals may be viewed as an adaptive response and protective mechanism against a metal-pesticide-induced oxidative stress.…”
supporting
confidence: 87%
“…Elevated levels of plasma total cholesterol (TC) and triglycerides (TG) have been implicated as causative factors in development of atherosclerosis and coronary heart diseases (CHD). Efforts to develop effective and better hypolipidaemic drugs have led to the discovery of natural agents [15]. Research in herbal medicine has increased in the world as an alternative solution to health problems so the aim of present study was to determine the effects of the Anethumgraveolensextract on serum lipoproteins profile in hypercholesterolaemic mice.…”
Section: Introductionmentioning
confidence: 99%